Perbandingan Algoritma Reduksi Tipe pada Fuzzy Tipe-2 - Humaira, Mira (MATICS, 2014)
Type-2 Fuzzy became populer because it’s capability handles uncertainty more better. It effects computational cost. This research insurance that there is algorithm having good performance ie. EIASC. It has short time if count of N is small. Index Terms—EIASC Algorithm, Type-2 Fuzzy